Pandemic Apocalypse In Between Dystopias: Observations from Post-Apocalyptic Novels - Munir Ahmed Al-Aghberi (Angles)
Investigating the novels that deal with a pandemic apocalypse, this study highlights the dystopian elements preceding and following the end of the world. Inspired by the COVID-19 pandemic in the 21st century, it relates the fears of the pandemic to the literary history and political conditions nurturing that imagined end of the world in a number of post-apocalyptic novels. The novels are examined under three tropes: the early novels prophesying a 21st-century apocalypse; the postwar novels linking the plague to power conflicts; and the recent novels tackling biogenetic experimentation. The study pulls apart, with a limited depth, the parts played by the political and economic world systems in bringing about the pandemic apocalypse as well as the dystopian aftermaths. It concludes that although the novels lash a critique against capitalist recklessness, they ambivalently suspect the existence of a viable alternative.